Islam liberal and its ideological challenges to Muslim's beliefs and practices: an analysis - Abdul Rahim, Adibah (2022)
Islam liberal is one of the dangerous ideological assaults facing the Muslims today. It may affect the aqidah of Muslims and subsequently destroys Islam itself. Unlike other Western modern ideologies, Islam liberal is debating issues based on Qur’anic verses, hadith, opinions of ‘ulama’, and employing the Islamic keywords. In addition, Islam liberal is supported by Muslim scholars who are coming from a religious background. They claimed that they represent the moderate Muslims to cleanse the image of Islam which has been labelled as religion of terrorism, fanaticism, anti-Western, and anti-modern. Their approach was to save Islam from rigidity and to defend it based on liberal progressive thinking. As such, Islam liberal seems to be easily accepted by Muslim society. However, Islam liberal posed serious challenges to the Muslims due to issues it advocates and its ideological principles which are incompatible with the views of Qur’an and Sunnah as well ahl sunnah wal jama’ah.